SCHOLARSHIP APPLICATION FOR STUDENTS ELEMENTARY LEVEL (ELEMENTARY SCHOOL) DEPARTMENT OF EDUCATION AND CULTURAL SUB BRANCH CILEDUG TANGERANG USING MICROSOFT VISUAL BASIC VERSION 6.0. - Emi Sudaryanti (Jurnal Sistem Informasi, 2010)
Education is essential for human life, but not everyone can feel a decent educationbecause of the increasing cost of education. For a little overcome this, the governmentallocated funds to provide scholarships, which often occur in the process ofdisbursement delays due to a delay in processing the data. With advances in computertechnology, as now, we are facilitated with a variety of applications that can helpdata-processing activities. Therefore, the writer tries to create an application that canspeed up data processing.